Rootstock identity in melon-pumpkin graft combinations determines fruit metabolite profile - Camalle, Maria Dolores; Pivonia, Shimon; Zurgil, Udi; Fait, Aaron; Tel-Zur, Noemi (Frontiers in Plant Science, 2023)
Grafting has the potential to improve melon fruit yield and quality, but it is currently held that a lack of compatibility between the rootstock and scion compromises such an effect. To throw light on this subject, we studied melon-pumpkin graft combinations with different levels of compatibility to assess to the effect of the rootstock identity on melon fruit yield and quality, including total fruit ortho-diphenols, total flavonoids, and primary fruit metabolites. Melon cv. ‘Kiran’ (Ki) was grafted onto three pumpkin rootstocks, ‘TZ-148’ (TZ), ‘Shimshon’ (Sh), and ‘53006’ (r53), characterized by high, moderate, and low compatibility, respectively. The non-grafted melon cultivar Ki was used as the control. The incompatible combination Ki/r53 gave the lowest fruit yield and the lowest average fruit weight. In that combination, the content of total ortho-diphenols increased vs. Ki and Ki/TZ and that of total flavonoids decreased vs. Ki/Sh. In addition, concentrations of the amino acids, glutamate, methionine, valine, alanine, glycine, and serine, increased in the pulp of the two compatible combinations, i.e., Ki/TZ and Ki/Sh, suggesting that rootstock identity and compatibility with melon Ki scion modulated amino acid synthesis. Our results show an association between rootstock identity (and level of compatibility with the scion) and an enhancement of fruit nutritional values, i.e., high concentrations of organic acids (determined as citrate, malate, fumarate, and succinate) and soluble carbohydrates (sucrose) were recorded in the pulp of the two compatible combinations, i.e., Ki/TZ and Ki/Sh.